Photoinduced site-selective alkenylation of alkanes and aldehydes with aryl alkenes - Hui Cao (Nature Portfolio, 2020)
Dehydrogenative alkenylation of C-H bonds is an atom-economical approach to prepare more complex olefins. Here, the authors use a combination of decatungstate and a cobaloxime catalyst for the photocatalytic dehydrogenative alkenylation of alkanes and aliphatic aldehydes with aryl alkenes.